De-epithelialization technique as an esthetic treatment for gingival lichen planus - Marcelo Hissao Imano; Luiza Foltran de Azevedo Koch; Paula Porto Spada; Marilisa Carneiro Leão Gabardo; Tatiana Miranda Deliberador (Editorial Ciencias Médicas, 2021)
Introduction: Oral lichen planus is a chronic inflammatory disease affecting the mucosa. Objective: To report a clinical case of oral lichen planus in gingiva whose removal was carried out by the de-epithelialization technique of the affected areas. Case report: A 56-year-old female patient presented white plaques upon clinical examination that could not be removed by scraping. The treatment plan involved a biopsy and lesion removal by de-epithelialization, procedure not described in the literature up to date. This technique consisted of the removal of the plaques with the epithelial tissue from the gingiva using a 15c blade, leaving the connective tissue exposed. Clinical follow-up was performed at 3 and 10 days, and at 2, 3 and 15 months. Conclusions: De-epithelialization was a resolutive esthetic intervention for the case presented.